Visual Evidence: Increasing Usability of Systematic Reviews in Health Systems Guidelines Development - Smith, Connor J.; Jungbauer, Rebecca M.; Totten, Annette M. (Applied Clinical Informatics, 2019)
Background Integration of evidence from systematic reviews is an essential step in the development of clinical guidelines. The current practice for reporting uses a static structure that does not allow for dynamic investigation. A need exists for an alternate reporting modality to facilitate dynamic visualization of results to match different end-users' queries.Objectives We developed a dynamic visualization of data from a systematic review using the commercial product Tableau and assessed its potential to permit customized inquiries.Methods Data were selected and extracted from a previously completed systematic review. The resulting dataset was then used to develop an interactive, web-based report designed for use by a guidelines development committee.Results A novel example of combining existing reporting standards for systematic review data and modern reporting tools was developed to investigate potential benefits of a dynamic report. Demonstrations of the report to clinicians sitting on previous and future guideline committees received positive feedback for its potential benefit in guidelines development. The report received a runner-up award during the design challenge at the 2018 Workshop on Visual Analytics in Health Care.Conclusion The use of interactive, accessible data may increase the use of systematic reviews and aid decision makers in developing evidence-based practice changes.
Keywords: data visualization; clinical informatics; clinical practice guidelines; systematic reviews; data access; integration and analysis; evidence-based medicine and nursing; guidelines and protocols; evaluation